Medico Legal Awareness:Where are we? – A Survey among Health Professionals in Maharashtra and Haryana - Mayuresh, J. Baheti; Sampada, Thakur; Ronak, Khokhani; Preetam, Mahagaonkar; Nandlal, Girijalal; Gangadhar, S.A. (Universiti Kebangsaan Malaysia, 2015)
Introduction: Medicine is a noble profession but there is also growing anxiety both within the medical profession and in the community regarding increasing trends of complaints and lawsuits against doctors. Knowledge about medical ethics is as fundamental to the practice of medicine as clinical skills. To assess the knowledge of health care professionals regarding medico-legal issues. Methods: The questionnaire study consisted of questions pertaining to basic knowledge of COPRA (Consumer Protection Act 1984), informed consent and Medicolegal courses. A total of 325 health care professionals enrolled for the study. Results: Most of the health care professionals were able to answer questions about informed consent. Almost 80% of health professionals were aware about informed consent, 41.84% of health professionals were not aware about consumer protection act 92%of health professionals don’t know about the courses regarding Medico-legal issues. Conclusions: The participants were knowledgeable about medical ethics and informed consent but when it came to Consumer Protection act, professional indemnity claim and medico- legal courses their information was basic, they lacked knowledge about finer details hence showed an immediate need to update the understanding of these issues to be on legally safer side.